Filtration rate of the marine clam (Katelysia sp) at different algal concentrations and body size. - Caspe, Raymond
The effects of algal concentration on the feeding behavior of the clam were determined using indirect method of suspension depletion and monitored by direct algal cell count. The different algal concentrations used in this experiment were 1x10 raised to the 5th power, 2.5x10 raised to the 5th power and 5.0x10 raised to the 5th power cells/ml. Results showed that the highest filtration race of clams at different concentrations of Isochrysis galbana was at 2.5x10 raised to the 5th power cells/ml which is the moderate concentration used followed by the highest algal concentration of 5.0x10 raised to the 5th power cells/ml. Least filtration rate was observed at the lowest algal density of 1x10 raised to the fith power cells/ml. the moderate concentration appeared to be the maximum concentration that the gills of the clams can hold. Clams tend to lower their filtering activity when exceeded in the threshold level to protect their digestive system. It was also observed that filtration rate was high in the first thirty minutes of the experiment and decreases as the experiment continues. clams tend to have a high "appetite " in the first part of the experiment due to large number of algal cells and because they wee starved for 12 hours., The second part of this experiment was cocerned with the effect of body size on the feeding behavior of clams. Due to insufficient supply of the clams during the conduct of this study, only two size classes were done. The smaller body size ranged from 40 to 49.99mm and the bigger body sized clams ranged from 50 to 59.99 mm. Results of this experiment showed that smaller body sized clams have higher filtration rate compared to the bigger sized clams.